Book Excerpt: The Mists of Cyberhenge: Mapping the Modern Pagan Internet - Cowan, Douglas E (Pomegranate, 2007)
Since its popular inception in the mid-1990s, the World Wide Web has been subject to a set of interrelated mythologies about its potential as a social technology. Virtual reality has been confused with online activity, the question of computer-mediated community has been debated, and researchers have begun to explore the Internet’s impact on religious belief and practice. This excerpt addresses some of these concerns in terms of the Internet more generally and modern Paganism on the Internet more specifically. While some Pagans regard the Net as the next leap in magickal evolution, others consider it little more than a global notice board for the privileged classes.